Ovarian Adenomatoid Tumor Coexisting with Mature Cystic Teratoma: A Rare Case Report. (11th September 2017) - Shi, Mingxia; Al-Delfi, Firas; Al Shaarani, Majd; Knowles, Kurt; Cotelingam, James
Abstract : Adenomatoid tumor of the ovary is rare, and so are collision tumors in this location. The most common histological combination of ovarian collision tumors is the coexistence of mature cystic teratoma with ovarian cystadenoma or cystadenocarcinoma. Presented herein is a rare case of ovarian adenomatoid tumor found incidentally and coexisting with mature cystic teratoma. A 44-year-old woman presented with a one-year history of intermittent right-sided pelvic pain. Ultrasound evaluation revealed a heterogeneous cystic mass in the right ovary, and a clinical diagnosis of teratoma was made. The patient subsequently underwent a right salpingo-oophorectomy. Pathological examination revealed a mature cystic teratoma and coexistent adenomatoid tumor. The two tumors were separate and no transitional features were recognized histologically. To our knowledge, no previous report of coexistence of these two tumors has been reported. Both tumors are benign and completely excised; therefore no adverse consequences are expected.